(untitled) (International Journal of Environmental Sciences, 2025)
Background: Hepatocellular carcinoma (HCC) is the 3rd leading etiology of cancer-related mortality worldwide and the 6th most prevalent tumor overall. Aim: To evaluate the comparative effectiveness of conventional transarterial chemoembolization (TACE) and drug-eluting beads TACE (DEB-TACE) in treating unresectable liver carcinoma. Patients and methods: This prospective investigation involved 75 cases with unresectable hepatocellular carcinoma managed with conventional Transarterial Chemoembolization (TACE) in Group I (n=42) or Drug-Eluting Bead Transarterial Chemoembolization (DEB-TACE) in Group II (n=33) at the National Cancer Institute in Cairo from 2019 to 2023. Results: Both groups showed comparable clinical parameters. Group I’s tumor load ranged from 2.1 to 8.3 cm (mean: 4.18 cm, SD: 1.93) and AFP levels from 304.4 to 1760.3 (mean: 1157.75, SD: 344.8), while Group II had a tumor load from 2 to 9.1 cm (mean: 4.48 cm, SD: 2.04) and AFP levels from 118.3 to 2582.6 (mean: 1280, SD: 573), with no significant distinctions (P=0.5169 and P=0.2552, correspondingly). Treatment responses were also similar, with both groups showing nearly identical distributions of complete, partial, stable, and progressive disease (P=0.998). However, regarding adverse effects, nausea and abdominal pain were significantly more frequent (P=0.0126 and P=0.0282, correspondingly), while vomiting rates remained comparable between the groups. Conclusion: Both procedures, cTACE and DEB-TACE, are efficient in the management of intermediate stage hepatocellular carcinoma with no statistically significant superiority of DEB-TACE. Fewer complications are noticeable with cTACE in comparison with DEB-TACE.